Temperature and field dependence of the flux pinning mechanisms in Fe1.06Te0.6Se0.4 single crystal. (November 2016) - Hossaini, S.J.; Ghorbani, S.R.; Arabi, H.; Wang, X.L.; Lin, C.T.
Abstract: The temperature and magnetic field dependence of the magnetization and critical current density of Fe 1.06 Te 0.6 Se 0.4 single crystal have been investigated, and the flux pinning mechanism has been analyzed. The critical current density results indicate that there are different pinning mechanisms in this crystal. The pinning mechanisms are studied in terms of the pinning model where the normalized volume pinning force, f p, versus h = H / H irr, where H irr is the irreversibility, were studied systematically. It was found that a variety of pinning mechanisms including normal point pinning, normal surface pinning, and pinning based on spatial variation in the Ginzburg-Landau parameter (Δ k pinning) pinning mechanisms coexist. The effects each of the different pinning mechanisms were obtained. The results show that the contributions of the real pinning mechanisms are dependent on the temperature and magnetic field in this the single crystal. Highlights: The J c results suggest that excess Fe in Fe 1.06 Te 0.6 Se 0.4 single crystal improves the pinning potential and results in enhancement of the J c . A variety of pinning mechanisms, e.g. normal point pinning, normal surface pinning, and Δ k pinningpinning mechanisms coexist in Fe 1.06 Te 0.6 Se 0.4 single crystal. The pinning mechanisms effects depend on both the temperature and the magnetic field.